3D markerless motion capture in Olympic sport disciplines - Hock, T.; Pickardt, S. (Sports Tech World Series: Europe Sports Tech Conference Series - Event 6: Technical Performance & Data Science, 2020)
New methods in machine vision and artificial intelligence in 3D Markerless Motion Capture Technology enable more easy, detailed and enhanced Analysis of athletes in various sports. Especially sports with a high demand on the individual technique like track & field or gymnastics will benefit from these new technologies. Performance Center like the Institute of Applied Training Science Germany (IAT) shows new ways in using new technology for athlete development for the future. Thomas Hock, Business Development in Sport & Sales Manager Europe, Simi Reality Motion Systems GmbH Steven Pickardt, Institute of Applied Training Science